Effect of alcohol consumption on oncological treatment effectiveness and toxicity in patients with cancer: a systematic review and meta-analysis - Georgios Fountoukidis; Aglaia Schiza; Daniel Smith; Mukhrizah Othman; Marie Bergman; Johan Ahlgren; Mats Lambe; Sandra Irenaeus; Antonis Valachis (BMC Cancer)
Abstract Background Alcohol consumption has been associated with an increased risk of cancer-related mortality. It may also negatively impact oncological therapies, potentially leading to impaired effectiveness or an increased risk of treatment-related toxicities. The aim of this systematic review and meta-analysis was to examine the current evidence regarding the potential effects of alcohol consumption during cancer treatments on both treatment effectiveness and toxicity, irrespective of cancer type. Methods A comprehensive literature search was performed across three electronic databases (Medline, Web of Science, Cochrane) covering studies from January 1990 to December 2023. Furthermore, a manual search based on the reference lists of the eligible studies was performed to identify additional potentially eligible studies. Studies were eligible if they involved cancer patients and provided data on alcohol consumption during specific oncological treatments, including its effect on treatment outcomes, or compared treatment effectiveness or toxicity between drinkers and non-drinkers. Studies were excluded if they did not meet these criteria, were duplicates, case reports, conference abstracts, or focused only on cancer-specific or overall survival. Only studies using multivariable analyses to examine the association between alcohol consumption and treatment effectiveness or toxicity were included in the pooled analyses. Pooled Hazard Ratios (HRs) or Odds Ratios (ORs) and their corresponding 95% Confidence Intervals (CIs) were calculated using random-effects models. Study quality was assessed by using the Newcastle–Ottawa scale whereas the GRADE approach was applied to rate the certainty of evidence for pooled analyses. Results Out of 6734 studies identified through searching, 38 met the inclusion criteria for pooled analyses. Alcohol consumption during radiotherapy, with or without concomitant chemotherapy, was associated with worse disease-free survival (pooled HR: 2.05; 95% CI: 1.09 – 3.89), although the numerically increased risk for locoregional recurrence did not reach statistically significance (pooled HR: 2.01; 95% CI: 0.76 – 5.36). The potential impact of alcohol consumption on chemotherapy-induced neurotoxicity and acute / delayed nausea was not statistically significant. However, alcohol consumption was associated with a lower risk of overall chemotherapy-induced nausea (OR: 0.69; 95% CI: 0.57, 0.84). Conclusion Our findings suggest that alcohol consumption may have a negative impact on radiotherapy, whereas its potential impact on the effectiveness of systemic oncological therapies (chemotherapy, molecular targeted therapy, immunotherapy, endocrine therapy) has not been adequately studied. Similarly, the current evidence on the potential association between alcohol consumption and treatment-related toxicities is weak, highlighting the need for well-designed prospective studies on this topic.